Model-Based Control of Biochemical Reactors (The Control Handbook, 2011)
The biotechnology industry is expanding rapidly due to continuing advances in the understanding of complex biological systems and the high demand for biologically manufactured products such as foods andbeverages, pharmaceuticals, and commodity and specialty chemicals. The impact of the biotechnology industry on the global economy is substantial. For example, the revenues of the top 10U.S. pharmaceutical manufacturers totaled USD 217 billion in 2002 with profits of USD 36 billion [1]. A rapidly growing biotechnology market is the large-scale production of ethanol as a renewable liquid fuel. The production of ethanol in 1998 was 31.2 billion liters worldwide and 6.4 billion liters in the United States with roughly two-thirds of the ethanol produced targeted for biofuel applications [2].